Children as change makers : a resource to enhance child centred practice and extend active learning opportunities - Frankel, Sam (Emerald studies in child centred practice, 2024)
Inspired by narratives on children's rights, participation and social action, Children as Change Makers aids in creating active learning opportunities that will equip students in higher and further education, as well as practitioners and professionals to meaningfully get involved in community change projects that effectively partner with children and young people. The chapters reignite a call for a paradigm shift in society, arguing that children's social engagement is key to navigating local and global change. It invites adults to advance their thinking by reflecting on and revisiting the way they view children as participants (especially children under the age of 12 years old). Drawing on the multidisciplinary field of Childhood and Youth Studies, Sam Frankel and Daniella Bendo call for a unity of thought that equips children and young people as 'participants' to be a catalyst for a shared vision that recognises the social, environmental, economic and health challenges in communities. Children as Change Makers will increase children's, students, and practitioners' confidence by engaging with guidance, practical examples and activities to strengthen collaborative opportunities with children. Drawing on a new innovative active learning approach, this book aims to bolster academic, professional and community learning opportunities and create experiences that contribute to life skills, career ambitions, and goals.